A New Edition Which Is Not So New:A Critique on the Most Recent “Edition” of Avicenna’s Dānešnāmeh-ye ʿAlāyī - Hanif Amin Beidokhti (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Here, I examined the most recent “edition” of Avicenna’s Dānešnāmeh-ye ʿAlāyī published by Mawlā Publishing house. With this aim, I provided an overview of the editorial and publishing genealogy of the Dānešnāmeh, and then of Mawlā’s edition. I considered a number of errors and shortcomings exhibited by the latter, whilst acknowledging some of its merits. Identifying certain systematic flaws in the editorial techniques that inform Mawlā’s edition, on the one hand, and a structural mistake that has entirely ruined one of the main philosophical innovations of the Dānešnāmeh, on the other hand, I detected that Mawlā’s “edition” is an unprofessional reprint of the previous editions done by Moʿīn, Meškāt and Bīneš. I observed that the long preface to the text bears no relation to the Dānešnāmeh, and provides scholars with no useful insight into either Avicennan philosophy or the Dānešnāmeh. Concluding that Mawlā’s “edition” is woefully lacking, I suggest that it has no advantage over the previous standard editions.